PEMANFAATAN WAKTU BELAJAR SISWA DILUAR JAM BELAJAR SEKOLAH PADA SISWA SMA NEGERI 1 BANGKINANG - Desmi Wirdatul Hasana; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The title of this study is the Utilization of Student Learning Time Outside School Learning Hours In High School Students 1 Bangkinang. This study aims to determine (1) how the use of free time in school with learning activities. (2) How to use free time outside school with learning activities. (3) How is the relationship of learning achievement with the utilization of leisure time. The subject of this research is the entire class XI consisting of 5 classes each class taken 17 students. The population in this study is 113 students, the number of samples taken 85 students. The sample here is by simple random sampling technique. This research was conducted in SMA Negeri 1 Bangkinang. The reason for choosing a school because it wants to see how the use of leisure time students who go to school in the countryside. This research method is quantitative descriptive. To collect research data using questionnaire, observation and documentation.The result of correlation test showed that the relationship of expenditure time variable in school has an effect on the achievement and the variable of the utilization of leisure time outside the school has an effect on the achievement and we can see from the final result of the recap presented in table form in this thesis shows the lack of students' The final result is 69.75%, it is categorized as being in the use of free time both at school and home because it is between 50% - 75%.Keywords: utilization of leisure time, learning achievement